Throwing accuracy. (14th March 2018) - Cross, Rod
Abstract: A simple throwing task is described to illustrate various aspects of projectile motion. The task was to throw a tennis ball in a waste paper bin about 2 m away. Success depends on skill, but it also depends on the physics of the problem. If the ball is thrown underarm, then success depends primarily on the throw speed, which must be controlled to within about 2%. The launch angle can be chosen within a wide range. If the ball is thrown overarm, then the launch angle is just as important as the throw speed.